La felicidad organizacional (2018)
This text exposes a detailed research of a relevant topic nowadays, not only in the daily life, but also in the job environment, the Happiness, since throughout the years there have gone away created innumerable documents, actions, workshops, between other mechanisms that have allowed the companies to implement these factor of basic character, which in some companies has taken as something without major incident in the work, but that along the study there will be demonstrated that your implementation in the labor actions of the company is crucial in order that the worker feels identified and with belonging inside the community of your companions of work and employers; for ende this work was approaching concepts from happiness, since one sees involved and your relevancy, the human factor represented as human resource that was taking charge guaranteeing the comforts of the worker and guarding over your well-being that turns out to be the synonymous one of happiness; they were presenting advices and definitions that will allow to the reader to be identified by every aspect and characteristic that it is necessary to bear in mind from the simplest thing up to the most complex thing in the search of the way that leads the worker to finding this happiness so longed that one will allow him to unroll and to work in a more productive way, strengthening the bows with the company and this way to realize your work with sense of belonging, which is for what the chief looks to guarantee a good production and better sales; putting as basic factor the happiness of the worker.